Pengembangan Sistem Self-Service Reservation pada Everyday Smart Hotel Malang Menggunakan Customer Relationship Management (CRM) Operasional Modul Sales Force Automation dan Service Automation - Farhan Ishami; Retno Indah Rokhmawati; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Customer Relationship Management (CRM) is the process of menaging interaction between companies and customers regarding sales and service who utilize some integrated information to understand customer behaviour and serve the best service. This research was held at Everyday Smart Hotel Malang which one of activities is reservation process.Currently, the ordering has two process through online travel agent and booking process directly. But on certain activites, many customers make reservation directly. Furthermore, ordering process is often the occurrence of long queues, information received by customers is not complete, so customers involved to leave Everyday Smart Hotel. Regarding of this case hence need operational Customer Relationship Ranagement (CRM) module Sales Force Automation (SFA) and Service Automation (SA) Customer Self-service activity in order to improve service and customer satisfaction by applying integrated web-based system information then it will be more efficient. The result of this Customer Relationship Management (CRM) system for effectivity aspect, the result was 96% for customers and 96% for receptionist. For efficiency aspect, average time result 80% for the customer and 83% for receptionist more efficient. Then, for user satisfaction, the result was better because it has sixteen statement good for customers and receptionist.